Comparison of hybrid capture II, linear array, and a bead-based multiplex genotyping assay for detection of human papillomavirus in women with negative pap test results and atypical squamous cells of undetermined significance. - Comar, Manola; Iannacone, Michelle R; Casalicchio, Giorgia; McKay-Chopin, Sandrine; Tommasino, Massimo; Gheit, Tarik (J Clin Microbiol, 2012)
Many methods with different levels of analytical sensitivity and clinical specificity have been developed to detect the presence of high-risk (HR) types of the human papillomavirus (HPV) in cervical samples. The Hybrid Capture II (HC-II) assay is broadly used for primary screening. In addition, several HPV genotyping assays, based on PCR methods, display higher sensitivity than the HC-II and are also used in screening programs. We evaluated the performance of three HPV DNA tests, namely, the HC-II, the Linear Array (LA) HPV genotyping assay, and an HPV type-specific E7 PCR bead-based multiplex genotyping assay (TS-MPG) that is a laboratory-developed method for the detection of HPV, in 94 women with atypical squamous cells of undetermined significance (ASC-US) and in cytological samples from 86 women with a negative Pap test. The HPV prevalence with the TS-MPG assay was increased compared to the prevalence with the LA and HC-II assays. The HPV DNA prevalence in women with ASC-US was greater with the TS-MPG assay (46.2%) than with the LA (36.3%) and HC-II (29.7%) assays. The HPV DNA prevalence in the control group was greater with the TS-MPG assay (32.1%) than with the LA assay (10.7%). Two women with ASC-US who were HPV DNA negative by the HC-II and positive by the TS-MPG or/and LA assays had lesions that progressed to low-grade squamous intraepithelial and high-grade squamous intraepithelial lesions. This study shows that the TS-MPG assay exhibited higher analytical sensitivity than the LA and HC-II assays for the detection of HPV DNA, which reduces the potential to incorrectly identify a woman's HPV infection status.
Keywords: Adult; DNA, Viral; Female; Humans; Molecular Diagnostic Techniques; Papillomavirus Infections; Sensitivity and Specificity; Uterine Cervical Neoplasms; Virology